2011
DOI: 10.1111/j.1751-553x.2010.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing hematopoietic microchimerism is a reliable indicator of incipient AML relapse

Abstract: Within this paper, we emphasize the importance of microchimerism monitoring as a reliable indicator of incipient AML relapse, especially in patients where no other specific molecular marker is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
2
14
0
2
Order By: Relevance
“…This is substantially earlier than most previous reports, although the heterogeneous nature of the literature complicates comparison. Studies in adults have reported a time interval to relapse of about 1 month . Two studies including children report a median of 125 and 144 days from first positive chimerism to relapse of myelodysplastic syndrome and AML, respectively .…”
Section: Discussionmentioning
confidence: 71%
“…This is substantially earlier than most previous reports, although the heterogeneous nature of the literature complicates comparison. Studies in adults have reported a time interval to relapse of about 1 month . Two studies including children report a median of 125 and 144 days from first positive chimerism to relapse of myelodysplastic syndrome and AML, respectively .…”
Section: Discussionmentioning
confidence: 71%
“…This finding, however, is controversial because some studies failed to demonstrate a correlation between mixed chimerism after HSCT and a higher risk for relapse [26,28,29]. Nevertheless, several groups established that increasing mixed chimerism is clearly associated with higher frequency of disease relapse in different hematopoietic malignancies [1,2,3,5,6,7]. Taken together, these data illustrate that the routine assessment of chimerism is a useful approach to evaluate post-transplantation prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, achievement of complete donor-derived hematopoiesis is one of the hallmarks of successful HSCT in hematopoietic malignancies. Moreover, several studies indicate that remaining or re-emerging recipient cells after ablation and transplantation are associated with a higher risk of disease relapse [1,2,3,4,5,6,7]. Therefore, the accurate and sensitive quantification of hematopoietic chimerism is a critical aspect of post-transplantation monitoring, since the results strongly influence the therapeutic approach such as donor lymphocyte infusions, additional chemotherapy, or re-transplantation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative PCR analysis using insertion/deletion polymorphism (indel qrtPCR) is a well-characterized and simple technique, which can be performed in peripheral blood with a better sensitivity compared with standard STR-PCR (0.01-0.1% vs 1-5%). 22,23 While this technique has been previously used by others, [24][25][26] its usefulness to predict relapse at the recipient's cell level o1% has never been clearly evaluated.…”
Section: Introductionmentioning
confidence: 99%